Profile of students at the Polytechnic Institute of Viseu : an evolutionary study since the Treaty of Bologna - Malva, Madalena (Millenium - Journal of Education, Technologies, and Health, 2021)
Introduction: This work intends to fazer a characterization of the typical individual of the Polytechnic Institute of Viseu (IPV), in general, and of each Organic Unit (UO), in particular. Never before has a comprehensive study been carried out that decreases the demographic origin of two students, or the way in which they enter IPV, which or type of course and which course is chosen. Além disso, seek relevant associations between some of these characteristics. This study allows, on the one hand, to meet or profile two students of IPV and, on the other, to develop strategies for the recruitment of new students. Objectives: To characterize the students enrolled, for the first time, not the Polytechnic Institute of Viseu, since or the beginning of the Treaty of Bolonha, or later, from the year 2006/2007 and until the year 2020/2021. Establish or profile two IPV students, generally, and two students from each Organic Unit, in particular: - ESEV (Higher School of Education of Viseu) - ESAV (Escola Superior Agrária de Viseu) - ESSV (Escola Superior de Saúde de Viseu) - ESTGV (Higher School of Technology and Management of Viseu) - ESTGL (Higher School of Technology and Management of Lamego) Methods: With recourse to descriptive and inferential statistics, it is possible to make an assessment on those who have entered non-IPV from the Bolonha Treaty. Description and sociodemographic analysis of two students, bem as or type of course sought without IPV, generally, in UOs, in particular. Or it was studied and complemented with a description and analysis of the entry form of two to some bachelor's degrees. Results: Among the withdrawn conclusions, we highlight that between 2006/2007 and 2020/2021, inscreveram-se, no IPV, 10573 (44.4%) homens and 13219 (55.6%) mulheres. On average, some 23.21 years old with a standard deviation of 7.56 years. Relatively to the district of origin, two students, mostly Viseu (61.5%), plus the districts of Aveiro (10.5%), Porto (5.2%) and Guarda (5.0%) contribute a significant percentage of students to or IPV. Quanto às NUTSIII, more than two students from Viseu Dão Lafões (51.5%), being Douro (11.7%), Porto Metropolitan Area (5.8%), Aveiro Region (6.6%) and Beiras and Serra da Estrela (4.7%) are units of where they provide a significant number of students. In the form of income, bachelor's degrees and gender are related (p-value = 0.000). Despite the relationship being failure (18.4%), there are more people to enter CTeSP / CET hairs, more than 23 and transfer (69.5%, 55.9% and 61.3%, respectively), and more women to enter the national access contest (62.3 %). Relating to the form of income from the degrees, it is verified the existence of a relationship significant (p-value = 0.000) and strong (62.8%). Conclusions: As expected, most of the people over 35 years old entered by over 23 (61.3%) and most of the people over 22 years (inclusive) entered the national access contest (90.9%). Similar findings were withdrawn for all IPV organic units.